TRIZ-Based Remodeling of Body Enclosure for Corpse - Ashley Edward Roy, Soosay; Muhammad Hamdi, Mahmood; Mohd Saiful, Bahari; Narayanan, Kulathuramaiyer (Springer Nature Switzerland, 2022)
This project started as an effort to gauge the epidemiological study for Road-Traffic-Accident (RTA). The data collected enabled us to make a Personalised product for management of the deceased. The deceased-on-site need to be handled with respect, compassion and safety in mind. For this purpose, a body bag is required. The nature of the death requires this body bag to work efficiently in various situations for example during accidents, arson, infectious disease death and other criminal acts. Currently the available body bag is a one-size-fits-all and at the same time the body bag poses a health hazard of exposure to harmful microorganisms for the forensic workers. This obvious contradiction suggests an inventive problem. The technical and physical contradiction in this particular problem allowed us to use TRIZ to better understand and discover a solution for the existing problem. Using TRIZ we were able to come up with Body Enclosure for Corpse (BEC). This product stands out as a solution for forensic workers and psychologically supports the family members of the deceased.